NFATC1 and NFATC2 expression patterns in human osteochondromas. Issue 1 (January 2023) - Wang, Yuanyuan; Ren, Jiangdong; Hou, Guojin; Ge, Xianpeng
Abstract: Background: Our previous study in genetic mouse models found that NFATc1 and NFATc2 suppress osteochondroma formation from entheseal progenitors. However, it remains unclear whether NFAT signaling is also involved in human osteochondromagenesis. As the first step in addressing this question, the current study aimed to determine the expression patterns of NFATC1 and NFATC2 in human osteochondroma samples. Methods: Immunohistochemistry (IHC) was used to examine and analyze NFATC1 and NFATC2 expression in human osteochondroma samples. The human periosteum was used to map the expression of NFATC1 under physiological conditions by IHC. Furthermore, human periosteal progenitors were isolated and identified from the periosteal tissues of bone fracture healing patients. The expression of NFATC1 in human periosteal progenitors was characterized by Western blotting compared to human bone marrow stromal cells (BMSC). Results: The IHC results showed that the expression of NFATC1 was undetectable in most human osteochondromas cells, and only a small proportion of osteochondroma cells, especially clonally grown chondrocytes, showed positive staining of NFATC1. NFATC2 expression was also undetectable in most chondrocytes in human osteochondromas. The mouse and human periosteum showed a comparable ratio of NFATC1 positive cells (9.56 ± 0.80% vs 11.04 ± 2.05%, P  = 0.3101). Furthermore, Western blotting analysis revealed that NFATC1 expression was highly enriched in human periosteal progenitors compared to BMSC. Conclusions: NFATC1 and NFATC2 are undetectable in most human osteochondroma chondrocytes. The expression pattern of NFATC1 in human osteochondromas and the normal periosteum suggests that NFAT signaling could be suppressed during human osteochondromagenesis.